Tuākana/Teina Water Warriors Project: A collaborative learning model integrating mātauranga Māori and science - Phyllis Callaghan; Ripeka Paraone; Maiki Murray; Ngaikiha Tahau; Saffron Edgarton; Ewan Bates; Ewarini Ataria; Harero Heremaia; Nukutai Rupene; Emily Wilson; Lochlan Hanham; Daniel Soal; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
Our waterways, particularly in urban environments, are subject to increasing pressures from human activity. Similarly, urbanisation has irreversibly changed the Māori cultural experience of their natural world including freshwater ecosystems. The Water Warriors is a collaborative project between Te Pā o Rākaihautū and Hagley Community College that was established to look after the waterways and re‐connect rangatahi (youth) with these environments within urban Ōtautahi (Christchurch). Fundamental to this project was the opportunity to integrate science with mātauranga Māori as equally valid knowledge systems. In doing this, our pononga (students) will not have to wait until they are adults to enjoy and experience science through a Māori world view and through this work simultaneously bring to life a cultural narrative of science. This paper describes the Water Warriors initiative along with an active student voice reflecting on their experiences.